2007
DOI: 10.1016/j.ultsonch.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted crystallization (sonocrystallization)

Abstract: The positive influence of ultrasound (US) on crystallization processes is shown by the dramatic reduction of the induction period, supersaturation conditions and metastable zone width. Manipulation of this influence can be achieved by changing US-related variables such as frequency, intensity, power and even geometrical characteristics of the ultrasonic device (e.g. horn type size). The volume of the sonicated solution and irradiation time are also variables to be optimized in a case-by-case basis as the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
229
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(243 citation statements)
references
References 17 publications
10
229
1
3
Order By: Relevance
“…Of all of these, sonication is one of the most commonly used, versatile, and significant in that it physically pulverizes solid constituents, typically in a liquid-solid slurry, into smaller fragments of a more uniform size and simultaneously increases the degree of intermixing when multiple components are present. Under some conditions ultrasound can also induce chemical change in a system and more importantly to this work, enhance crystallization in [42,43]. Under such conditions acoustic waves drive bubble formation, growth, and collapse through cavitation, which creates localized temperatures as high as 5000 °C and pressures as high as 500 atmospheres that in turn can induce chemistry [44].…”
Section: Introductionmentioning
confidence: 76%
“…Of all of these, sonication is one of the most commonly used, versatile, and significant in that it physically pulverizes solid constituents, typically in a liquid-solid slurry, into smaller fragments of a more uniform size and simultaneously increases the degree of intermixing when multiple components are present. Under some conditions ultrasound can also induce chemical change in a system and more importantly to this work, enhance crystallization in [42,43]. Under such conditions acoustic waves drive bubble formation, growth, and collapse through cavitation, which creates localized temperatures as high as 5000 °C and pressures as high as 500 atmospheres that in turn can induce chemistry [44].…”
Section: Introductionmentioning
confidence: 76%
“…Ultrasound application results in a dramatic reduction in induction period, metastable zone width and altered supersaturation conditions. [10][11][12][13] This will have significant effect on co-crystallization process of non-congruent system like caffeine -maleic acid. The sonochemistry reports available to date on co-crystallization of caffeine -maleic acid have used organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the lactose yield decreased with an increase in the protein concentration in lactose solution. It is known that at a short sonication time, the ultrasound waves fail to blend the solution and precipitate a little after sonication; at longer sonication time, more crystals precipitate at once but the average size of crystals becomes smaller with continuous sonication (De Castro and Priego-Capote, 2007). When the liquid medium (lactose solution) is exposed to ultrasound waves, alternating compression and expansion cycles are created.…”
Section: Effect Of Sonication Time On Lactose Yieldmentioning
confidence: 99%